The impact of electronic training on employee performance in the ready-made garments (RMG) sector of Bangladesh in the post-COVID-pandemic period - Ananna, Ahamadul Islam (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2024.